Implementasi Metode Syawir dalam Pelajaran Kitab Kuning di Kelas X MA Al Mahrusiyah Lirboyo Kediri - Bahrul ‘Uluum; Reza Ahmad Zahid; Abbas Sofwan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
MA Al Mahrusiyah has a yellow book subject. The local content of the yellow book subject was chosen by MA Al Mahrusiyah because this school is based on an Islamic boarding school and is also a local content of this school. This makes the researcher want to know more about the application of the yellow book subject applied in the scope of formal institutions, as well as providing a research problem formulation here, namely, how does the Syawir method affect the ability to read and write yellow books at MA Al Mahrusiyah Lirboyo, Kediri City. Here the author focuses the research by implementing the Syawir method which is a classic method in Islamic boarding schools by applying it in formal institutions, aiming to find out whether there is a very significant difference in students' reading and writing abilities in learning. The author uses a descriptive qualitative approach method. The research data sources consist of yellow book subject teachers, class X students, and learning documents. Data collection techniques are carried out through observation, in-depth interviews, and documentation, data analysis with the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of the syawir method goes through several stages, namely starting with the teacher reading the yellow book text and explaining it, students writing what the teacher explained, then the teacher sees the students' responses in implementing this syawir method, and the obstacles found by the teacher in implementing the syawir method. The research here is presented starting from the background of the research object, its components, a glimpse of the state of MA Al Mahrusiyah Lirboyo Kediri, and explains how the process of classroom learning is applied by the teacher to his students. Which affects the understanding of the yellow book subject which is a local content in this school